Photodynamic therapy in the treatment of patients with mycosis fungoides - E. V. Filonenko; V. I. Ivanova-Radkevich (Biomedical Photonics)
The review highlights the current understanding of the epidemiology, etiology, pathogenesis, existing classifications of mycosis fungoides. Methods for diagnosis and treatment of the pathology are described, among which photodynamic therapy (PDT) plays an important role. The main advantages of PDT for mycosis fungoides include the absence of systemic toxicity, non-invasiveness, selectivity, absence of carcinogenic potential, the possibility of repeated courses of treatment, and good cosmetic results. This review collects and analyzes the results of clinical trials of PDT in patients with mycosis fungoides. The analysis showed high efficiency of PDT in patients with mycosis fungoides with isolated or limited spots and plaques. PDT can be considered as the therapy of choice in patients with facial lesions when a good cosmetic result is one of the main requirements, and radiation therapy, nitrogen mustard or carmustine can leave permanent and visible scars. Plaques located in the axillary or inguinal skin folds that are inaccessible to phototherapy can also be treated with PDT.